The Republican Constitution seventy years later (Società e diritti, 2018)
Seventy years are passed from when the republican Constitution has gone to effect. It has legally made binding ethical principles, that are at the base of the protection of the inviolables rights of the man. It fully stays actual. This has not prevented but certain norms you are not correctly been applied and these - particulary the form of government - need suitable reformsKey words: Constitution, Moral principles, Reforms